JENIS-JENIS TUMBUHAN SUKU FABACEAE, SUBFAMILI CAESALPINIOIDEAE DI AREAL KAMPUS UNIVERSITAS TADULAKO, PALU - Rahmita, Rahmita; Ramadanil, Ramadanil; Iqbal, Moh. (Univ. Tadulako, 2019)
Research on the species of Plants of the Fabaceae Tribe Subfamili Caesalpinioideae at the area of Tadulako University Campus has been conducted from January to April 2019. This study aims to record, describe and determine the invasive status of plant species Fabaceae subfamili Caesalpinioideae. The research was based on botanical exploration method. The results showed there were 10 species from subfamily Caesalpinioideae including Acacia farnesiana (L.) Willd., Albizia saman (Jacq.) Merr., Caesalpinia pulcherrima (L.) Sw., Cassia javanica L., Delonix regia (Hook.) Raf., Desmanthus virgatus (L.) Willd., Leucaena leucocephala (Lam.) de Wit, Mimosa pigra L., Mimosa pudica L., Senna siamea (Lam.) H.S.Irwin & Barneby. Number of Species have been used as protective plants (5 species), as ornamental plants (2 species) and potentially as invasive species (3 species).